Proceeding of the 2001 Winter Simulation Conference (Cat. No.01CH37304)
DOI: 10.1109/wsc.2001.977241
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of introducing simulation as a decision making tool

Abstract: Over the years, simulation models have been successfully built to observe the behavior of systems. Despite advances in the field and its growth in popularity, when simulation is to be introduced to an organization, there are challenges to be met including acceptance by staff, availability of staff to describe the various operations, existence of useful data, and management expectations. Organizations are continuously collecting data, which may lead one to believe that developing stochastic models of an organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…The challenge at this point is avoid spending too much time creating scenarios or making changes in the model, such that the time available to get a solution is over while the students continue generating tons of output data without sense. Poor planning in this post-analysis stage may lead no finding a solution or to get one without the required statistical support (Centeno and Carrillo 2001). Thus, the use of the model to go deeper in the analysis provides a robust problem solution, which is very important in real life applications.…”
Section: Postmortem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge at this point is avoid spending too much time creating scenarios or making changes in the model, such that the time available to get a solution is over while the students continue generating tons of output data without sense. Poor planning in this post-analysis stage may lead no finding a solution or to get one without the required statistical support (Centeno and Carrillo 2001). Thus, the use of the model to go deeper in the analysis provides a robust problem solution, which is very important in real life applications.…”
Section: Postmortem Analysismentioning
confidence: 99%
“…Failure to properly transferring simulation concepts may result in the technique not being used properly, creating professionals who are skeptical to the application of simulation in real problems. Inadequate exposure to simulation may result in a professional who develops unrealistic expectations about what is possible to attain with simulation, to the point that they may attribute to it some magical capabilities to predict the future (Centeno and Carrillo 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that as the technology is easier to use, there is less rejection to use it (Workman 2005). Actually, one of the challenges to use discrete event simulation modeling as decision support system are that many people do not know how to program a simulation code, they are not willing to spent time learning a programming code, or they adopt a skeptical attitude to the benefits of the simulation, such that will be easier for the users to reject the software instead of used (Centeno and Carrillo 2001). Considering this fact, the game interface runs over a spreadsheet, which is a common general software used generally in undergraduate courses such as production, finance, accounting, and so on (Rao et al 1998).…”
Section: Interface Designmentioning
confidence: 99%
“…Pure modeling approaches include simulation and network based approaches. Simulation models can be very thorough but are extremely time consuming and costly to build and maintain and can become cumbersome in the level of detail needed to make the model work (Centeno and Carrilli, 2001; Riddalls et al, 2000; Swaminathan et al, 1998; Shapiro, 2001; Pegden et al, 1990). Often, the time it takes to even collect the data to model the system can become cumbersome and this is compounded by the time it takes to input the data into the model.…”
Section: Modeling Approachesmentioning
confidence: 99%